2019
DOI: 10.9734/mrji/2019/v27i330099
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Crown Rot Disease of Banana Fruit and Eco-Friendly Quality Improvement Approach during Storage

Abstract: Introduction: The banana is the world’s most popular fruit crop. A complex of fungal pathogen is responsible for crown rot diseases of banana. Aims: The present study was designed to detect and characterize the crown rot disease of post-harvest banana (Musa paradisiaca) and also develop an alternative quality improvement approach to improve banana shelf-life during storage period. Study Design: A simplest general factorial experiment that was designed to control crown rot disease of banana using di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
(18 reference statements)
3
3
0
Order By: Relevance
“…The PCR products showed 650 bp length size which was similar to the first isolated pathogen PCR results. Jahan et al [42] reported similar results which support our [43,44,45]. Ehiobu and Ogu, [46] revealed that Manihot esculenta leaf extract was significant at 75 g/L, with 68.2% inhibition against B. theobromae fungus and leaf extracts of Discoria rotundata, and Colocasia exculenta also possess significant in vitro antifungal activities against B. theobromae at the same concentration.…”
Section: Discussionsupporting
confidence: 82%
“…The PCR products showed 650 bp length size which was similar to the first isolated pathogen PCR results. Jahan et al [42] reported similar results which support our [43,44,45]. Ehiobu and Ogu, [46] revealed that Manihot esculenta leaf extract was significant at 75 g/L, with 68.2% inhibition against B. theobromae fungus and leaf extracts of Discoria rotundata, and Colocasia exculenta also possess significant in vitro antifungal activities against B. theobromae at the same concentration.…”
Section: Discussionsupporting
confidence: 82%
“…The PCR products showed clear cut band of 650bp length size which is 100% similar to our first isolated fungus. Jahan et al [19] reported similar results for crown rot disease of banana fruit causing fungus which support our present findings. The above results confirmed the isolated fungus as Pichia kudriavzevii which is responsible for brown rot disease of Citrus sinensis fruit.…”
Section: Discussionsupporting
confidence: 92%
“…Choi et al [18] showed similar morphological and microscopic results for a fungal isolate from nuruk and the pathogen was identified as P. kudriavzevii. Jahan et al [19] observed cylindrical, septate and slightly rounded ends conidia under light microscopic evaluation in case of crown rot disease of banana which supports our present findings. In the growth profiling of the present fungal isolate, PDA medium was found to be best for growth and development.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Some essential oils and plant extracts have been found to have a similar antifungal activity to commercial fungicides used against crown rot disease. Jahan et al (2019) reported that the methanol extract of garlic, A. sativum, has similar fungicidal activity as chemical fungicides like carbendazim and kanamycin B against crown rot. Spraying emulsions of basil oil on bananas was observed to control anthracnose and crown rot in bananas stored for 21 days.…”
Section: Bananamentioning
confidence: 99%